Identification of potential receptors for surface proteins of Toxoplasma gondii in humans / Lai Meng Yee - Lai , Meng Yee (2018)
Toxoplasma gondii (T. gondii) is an obligate intracellular protozoan parasite that invades any nucleated cells in humans and other warm-blooded animals, with a great infection rate. Approximately 25% to 30% of the world’s human population is infected by T. gondii. Many proteins involved in T. gondii invasion have been characterized, and the contribution for parasite entry has been proposed. The identification of receptors or binding host proteins for surface antigens is an important activity throughout the study. A better understanding of the interplay between T. gondii and its hosts may provide a starting point for the discovery of novel therapeutics. The surface antigens (SAGs) of T. gondii play a major role during the host cell invasion process. In this study, the yeast twohybrid system was used to analyze the interaction of T. gondii SAG1 and SAG2 with the human host cell. Protein interaction was performed using commercial human cDNA in pGADT7-RecAB. A total of 39 and 25 clones which interacted with the respective SAG1 and SAG2 were detected based on a series of the selection procedures. Twenty-nine and 18 clones for SAG1 and SAG2 were sent for sequencing after colony PCR. Following analysis of sequencing results, Y187 cells transformed with each of these potential prey plasmids (22 and 13 prey clones of each SAG1 and SAG2) was mated with the respective Y2HGold containing pGBKT7-SAG2 or pGBKT7-SAG1 and Y2HGold (pGBKT7). Homo sapiens lysine rich coil-coiled (abbreviated as HLY) and Homo sapiens zinc finger (abbreviated as HZF) proteins were identified as potential candidate interacting with SAG1 and SAG2, respectively. The interaction were further examined by betagalactosidase assay and the enzyme activity between SAG1 and SAG2 with their host proteins were 449.4 U and 437.7 U, respectively. In comparison to positive control (424.3 U), both interaction between prey and SAG1 and SAG2 were demonstrated. The iv interaction between prey and bait proteins was further determined using coimmunoprecipitation assay. The result indicated the binding between these prey and SAG1 and SAG2 proteins were significant. Finally, with the aid of isothermal titration calorimetry (ITC) method, binding strength for recombinant pRSET-A-SAG1/pRSET-AHLY proteins and recombinant pRSET-A-SAG2/pRSET-A-HZF proteins were 0.0075 µM and 18.75 µM, respectively. Both thermodynamic curves revealed that there were exothermic and endothermic reaction for recombinant pRSET-A-SAG1/pRSET-A-HLY proteins and recombinant pRSET-A-SAG2/pRSET-A-HZF proteins, respectively. These prey proteins may serve as the potential drug candidates during the vaccination study in future